2017
DOI: 10.5435/jaaos-d-15-00710
|View full text |Cite
|
Sign up to set email alerts
|

Functional Bracing After Anterior Cruciate Ligament Reconstruction: A Systematic Review

Abstract: The effectiveness of postoperative functional bracing following ACL reconstruction remains elusive. Some data suggest that functional bracing may have some benefit with regard to in vivo knee kinematics and may offer increased protection of the implanted graft after ACL reconstruction without sacrificing function, range of motion, or proprioception. However, limited evidence exists supporting the use of routine functional bracing to decrease the rate of reinjury after ACL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Altered contralateral hip strategy with limited motion and attenuating forces about the injured knee during gait has been noted in those who did not pass return to sport testing at 6 months [36]. Functional knee bracing may have some benefit via in vivo knee kinematics after ACL reconstruction; however, there is limited evidence that functional knee bracing decreases the rate of re-injury based on a systemic review of 15 studies [37].…”
Section: Late Post-operative Complicationsmentioning
confidence: 99%
“…Altered contralateral hip strategy with limited motion and attenuating forces about the injured knee during gait has been noted in those who did not pass return to sport testing at 6 months [36]. Functional knee bracing may have some benefit via in vivo knee kinematics after ACL reconstruction; however, there is limited evidence that functional knee bracing decreases the rate of re-injury based on a systemic review of 15 studies [37].…”
Section: Late Post-operative Complicationsmentioning
confidence: 99%
“…This finding confirmed the previous literature that showed no advantage of a postoperative treatment with a stabilizing knee brace after ACLR. 10 11 12 13 14 15 18 However, when we analyzed separately the patients who had concomitant surgery (ACLR-OI group), no differences were found in IKDC score between the braced and unbraced subjects.…”
Section: Discussionmentioning
confidence: 89%
“…However, disadvantages of bracing have been claimed, including the potential muscle atrophy, loss of knee extension at the removal, decreased patient's perception of maximal performance, increased fatigability during exercise, and additional costs. 12 13 14 15 18 Unfortunately, no evidence exists on effectiveness of bracing in patients with ACLR and concomitant surgery, 18 and this issue needs to be confirmed by further research.…”
Section: Discussionmentioning
confidence: 99%
“…When the outcome variable focuses exclusively on injury prevention several studies reported increased (29-31) rather than decreased knee injury rates and one specifically mentioned fear of decreased performance adversely influencing brace use compliance (32). For functional knee brace use post-ACL reconstruction, several studies have supported their potentially positive influences on knee kinematics, particularly lower leg rotational control (33)(34)(35)(36), while others have supported their use for improving hop distance symmetry, but not landing mechanics symmetry (37). Their use, however, does not appear to improve clinical outcomes (38,39).…”
Section: Resultsmentioning
confidence: 99%